Contribution of Adhesion to Bacterial Persistence in the Mouse Urinary Tract - Hagberg, L. (1983)
The affinity of uropathogenic Escherichia coli to kidneys and bladders of experimentally infected mice was shown to be determined in part by the adhesive properties of the infecting bacteria. Mice were infected with various pairwise combinations of two homogeneic sets of bacteria: (i) mutants derived from a human pyelonephritis E. coli isolate which were selected to express either or both adhesins specific for globoseries glycolipid receptors or for “mannosides”; and (ii) transformants of a normal fecal isolate which harbored recombinant plasmids encoding the genes for one or the other adhesin or which harbored only the vector plasmid. The relative efficiency of survival of the strains to be compared was evaluated in each animal by plating on selective media of samples of homogenized kidneys and bladders taken 24 h after intravesical inoculation. The presence of adhesins specific for globoseries glycolipid receptors, which mediate the in vitro mannose-resistant attachment to human and mouse uroepithelial cells, enhanced bacterial recovery from both kidneys and bladders of infected animals. The addition to the infecting strain of adhesins binding mannoside residues further improved bacterial recovery from the bladder, but not from the kidney. The mutants and transformants with adhesins binding only mannosides were recovered in higher numbers from the bladder than those expressing adhesins specific for the globoseries glycolipids only. There was apparent selection in vivo decreasing expression of mannoside binding adhesins in the kidneys, but not in the bladders, of animals infected with the mutant expressing both types of adhesins. Regardless of adhesive properties, the mutants of the pyelonephritis isolate were recovered in significantly higher numbers than the fecal isolate with adhesins encoded on recombinant plasmids. We conclude that the adhesive properties in part determine the localization and retention of bacteria in the mouse urinary tract. However, the addition of adhesins to a commensal E. coli strain was not sufficient to confer colonization capacity comparable to that of a pyelonephritis strain.